Effects of hemodialysis combined with hemoperfusion on severe acute pancreatitis - Zhenhe Li,; Guixia Wang,; Guodong Zhen,; Yuliang Zhang,; Jiaqiang Liu,; Shanmei Liu, (Turkish Journal of Gastroenterology, 2019)
Background/Aims: Severe acute pancreatitis (SAP) is characterized by persistent organ failure. This research aimed to evaluate the effect of hemodialysis combined with hemoperfusion on SAP. Materials and Methods: Thirty-seven patients who were treated with hemoperfusion combined with hemodialysis were included in group O, and 31 patients treated with conventional therapy and hemoperfusion were included as control (group C). Leukocyte count, neutrophil percentage, amylase (AMY), blood urine nitrogen (BUN), creatinine (Cr), and total bilirubin (TBIL) were noted. The time when symptoms disappeared as well as complications after treatment was recorded. Results: Leukocyte count, neutrophil percentage, AMY, BUN, Cr, and TBIL in two groups were remarkably decreased after treatment. However, these indexes were significantly lower in group O than those in group C after treatment, especially the neutrophil percentage, AMY, BUN, Cr, and TBIL. The time when the symptoms disappeared was 3.01±1.02 days in group O, which was shorter than 5.56±1.88 days in group C. There were 4 patients with acute renal failure and 2 patients had multiple organ failure in group C after treatment. But only 1 patient developed acute renal failure in group O. The difference in complications between two groups was significant (p<0.024). Conclusion: The combination of hemodialysis and hemoperfusion could have a better effect on SAP in removing toxic metabolites and inflammation mediators. It not only shortens the time of symptoms disappearing but also decreases the incidence of complications and the mortality. Cite this article as: Li Z, Wang G, Zhen G, Zhang Y, Liu J, Liu S. Effects of hemodialysis combined with hemoperfusion on severe acute pancreatitis. Turk J Gastroenterol 2018; 29: 198-202.